2022
DOI: 10.3390/molecules27217583
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone-1-Deoxynojirimycin Heterozygote Reduced the Blood Glucose Concentration and Alleviated the Adverse Symptoms and Intestinal Flora Disorder of Diabetes Mellitus Rats

Abstract: Chalcone-1-deoxynojirimycin heterozygote (DC-5), a novel compound which was designed and synthesized in our laboratory for diabetes treatment, showed an extremely strong in vitro inhibitory activity on α-glucosidase in our previous studies. In the current research, its potential in vivo anti-diabetic effects were further investigated by integration detection and the analysis of blood glucose concentration, blood biochemical parameters, tissue section and gut microbiota of the diabetic rats. The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Furthermore, studies related to the performance of the microbiome in drug metabolism, which directly influences its absorption and bioavailability, along with the potential of flavonoids to improve glycemia, as is the case with MPP, direct this research towards future studies on the possible mechanisms of action of MPP on the microbiota [59]. Studies with chalcone derivatives have also demonstrated this performance in the microbiota [60,61]. Investigations with derivatives of chalcones have related the anti-diabetic activity to its binding potential to the peroxisome proliferator-activated gamma receptor (PPAR-γ) [22,62].…”
Section: Anti-hyperglycemic Effectmentioning
confidence: 94%
“…Furthermore, studies related to the performance of the microbiome in drug metabolism, which directly influences its absorption and bioavailability, along with the potential of flavonoids to improve glycemia, as is the case with MPP, direct this research towards future studies on the possible mechanisms of action of MPP on the microbiota [59]. Studies with chalcone derivatives have also demonstrated this performance in the microbiota [60,61]. Investigations with derivatives of chalcones have related the anti-diabetic activity to its binding potential to the peroxisome proliferator-activated gamma receptor (PPAR-γ) [22,62].…”
Section: Anti-hyperglycemic Effectmentioning
confidence: 94%
“…Synthetic derivative that was supplemented (5,10,20 mg/kg BW, daily, 3 weeks) with DNJ (10 mg) as a control. The result was that the high dose lowered blood glucose of diabetic rats, more than DNJ or acarbose [168] Three chrysin-1-DNJ compounds, (Figure 9) These synthetic derivatives were tested for α-glucosidase inhibition, where compound 3 was most active [169] Fagomine with fi sh oil Pure compound, administered (0.96 g/kg BW, daily, 24 weeks) to diabetic rats, resulted decrease of blood glucose and insulin resistance [170] 15 N-DNJ This isotope labeled pure compound was isolated from Bacillus amyloliquefaciens and tested for safety of administration to diabetic rats. Safe.…”
Section: Figure 9 (Active Inhibitors)mentioning
confidence: 97%
“…237,238 Deoxynojirimycin and its derivatives, such as chalcone-1-deoxynojirimycin, improve gut microbiota disorders, increasing the Firmicutes to Bacteroidetes ratio in diabetic rats. 208,239 CAP influences gut microbiota by reducing Lactobacillus in T2DM mice while promoting beneficial bacteria, ultimately improving metabolic parameters. 240,241 Nuciferine supplementation affects gut bacteria, mitigating obesity by influencing key phylotypes and functions.…”
Section: Dietary Alkaloids On Gut Microbiotamentioning
confidence: 99%
“…208 DNJ-derived chalcone shows promise in managing gut health in diabetes. 239 Further research is required to explore the full potential of this compound.…”
Section: -Deoxynojirimycinmentioning
confidence: 99%